Komunikacja międzykulturowa a proces nauczania dorosłych francuskiego języka specjalistycznego jako obcego - Markowski, Grzegorz (Neofilolog, 2019)
The paper presents examples of techniques, strategies and activities by means of which a teacher of specialist French may improve the communicative competence level of their students, i.e. the communication skills and interculture competence. The suggestions presented will help the students to acquire the knowledge and skills necessary for functioning in the contemporary multicultural society. The aim is to prepare students for professional life by teaching them the correct use of specialist French in the institutions they are going to work for in the future.